Antibacterial potential of silver nanoparticles synthesized using Madhuca longifolia flower extract as a green resource. (August 2018) - Patil, Maheshkumar Prakash; Singh, Rahul Dheerendra; Koli, Prashant Bhimrao; Patil, Kalpesh Tumadu; Jagdale, Bapu Sonu; Tipare, Anuja Rajesh; Kim, Gun-Do
Abstract: The green and one-step synthesis of silver nanoparticles (AgNPs) has been proposed as simple and ecofriendly. In the present study, a flower extract of Madhuca longifolia was used for the reduction of silver nitrate into AgNPs, with phytochemicals from the flower extract as a reducing and stabilizing agents. The synthesized AgNPs were spherical and oval shaped and about 30–50 nm sizes. The appearance of a brown color in the reaction mixture is a primary indication of AgNPs formation, and it was confirmed by observing UV-visible spectroscopy peak at 436 nm. The Energy Dispersive X-ray spectra and X-ray diffraction analysis results together confirm that the synthesized nanoparticles contain silver and silver chloride nanoparticles. The Zeta potential analysis indicates presence of negative charges on synthesized AgNPs. The FT-IR study represents involvement of functional groups in AgNPs synthesis. Synthesized AgNPs shows potential antibacterial activity against Gram-positive and Gram-negative pathogens. M. longifolia flower is a good source for AgNPs synthesis and synthesized AgNPs are applicable as antibacterial agent in therapeutics. Highlights: Novel method for synthesis of silver nanoparticles. Silver nanoparticles act as an antibacterial agent against human pathogens. Green synthesized nanoparticles have been centered owing to its eco-friendly. Madhuca longifolia extract-mediated silver nanoparticles can be a potential antibacterial agent in therapeutics.